2017
DOI: 10.1371/journal.pone.0173394
|View full text |Cite
|
Sign up to set email alerts
|

Macrophage inducible C-type lectin (Mincle) recognizes glycosylated surface (S)-layer of the periodontal pathogen Tannerella forsythia

Abstract: The oral pathogen Tannerella forsythia is implicated in the development of periodontitis, a common inflammatory disease that leads to the destruction of the gum and tooth supporting tissues, often leading to tooth loss. T. forsythia is a unique Gram-negative organism endowed with an elaborate protein O-glycosylation system that allows the bacterium to express a glycosylated surface (S)-layer comprising two high molecular weight glycoproteins modified with O-linked oligosaccharides. The T. forsythia S-layer has… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
22
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 32 publications
(23 citation statements)
references
References 49 publications
1
22
0
Order By: Relevance
“…T. forsythia whole cells induced significantly greater amounts of IL-6 and IL-10 in wild-type (BALB/c) bone marrow-derived dendritic cells (BM-DCs) and macrophages, markers related to an M2-like polarization, as compared with TLR2 −/− cells. The macrophage-inducible C-type lectin receptor (Mincle), a Fc γ R-coupled pathogen recognition receptor (PRR) [ 263 , 264 ], has been reported to contribute to macrophage polarization [ 265 ]. THP-1 macrophages infected with the purified S-layer on whole wild-type T. forsythia elicit a M2-like polarization (IL-10, TNF- α ) that is limited in Mincle knockdown macrophages or where infection is performed with the S-layer TfΔtfsAB-mutated form [ 265 ] ( Figure 5 ).…”
Section: Macrophages In Periodontitis: Killers or Builders?mentioning
confidence: 99%
“…T. forsythia whole cells induced significantly greater amounts of IL-6 and IL-10 in wild-type (BALB/c) bone marrow-derived dendritic cells (BM-DCs) and macrophages, markers related to an M2-like polarization, as compared with TLR2 −/− cells. The macrophage-inducible C-type lectin receptor (Mincle), a Fc γ R-coupled pathogen recognition receptor (PRR) [ 263 , 264 ], has been reported to contribute to macrophage polarization [ 265 ]. THP-1 macrophages infected with the purified S-layer on whole wild-type T. forsythia elicit a M2-like polarization (IL-10, TNF- α ) that is limited in Mincle knockdown macrophages or where infection is performed with the S-layer TfΔtfsAB-mutated form [ 265 ] ( Figure 5 ).…”
Section: Macrophages In Periodontitis: Killers or Builders?mentioning
confidence: 99%
“…Factors that were also documented in literature related to Crohn’s disease are depicted in bold. References of the different ligands not mentioned in the text are for bacterial pathogen species ( 11 13 ), Leishmania ( 14 ), mycobacteria, and corynebacteria ( 15 , 16 ), Streptococcus pneumonia ( 17 ), Helicobacter pylori ( 18 ), Malassezia ( 19 , 20 ), Aspergillus fumigatus ( 21 ), Candida albicans ( 22 , 23 ), SAP130 ( 10 , 24 , 25 ), β-glucosylceramide ( 26 ), cholesterol crystals ( 27 ), and cholesterol sulfate ( 28 ). References for the various signaling molecules not mentioned in the text are for TLR4/MyD88 ( 29 ), PKC ( 30 ), vav proteins ( 31 ), HIF1α ( 32 ) and Nlrp3 ( 33 , 34 ).…”
Section: Minclementioning
confidence: 99%
“…It is known that Mincle recognizes diverse sugar-containing ligands including trehalose dimycolate glycolipid from mycobacteria, mannose-, glucoseor fucose-containing glycoconjugates, and Lewis antigen from Helicobacter pylori LPS (34). To note, it was recently reported that Mincle also recognize the O-linked oligosaccharides of the SLP from the Gram-negative oral pathogen Tannerella forsythia, and that interaction induces both pro-and anti-inflammatory cytokine secretion in macrophages (17).…”
Section: Discussionmentioning
confidence: 99%
“…Noteworthy, although the S-layer proteins were the first glycoproteins described in prokaryotes, the studies of the role of the glycan residues in the functional properties of these proteins are scarce and are usually focused on some archaea (16) or pathogenic bacteria (17,18). Regarding the genus Lactobacillus, there are some reports describing the involvement of the carbohydrate receptor DCspecific ICAM-3-grabbing nonintegrin (DC-SIGN) in the functional activity of the S-layer proteins from L. acidophilus NCFM (19), L. plantarum (20) and L. kefiri JCM 5818 (21).…”
Section: Introductionmentioning
confidence: 99%